2018
DOI: 10.3332/ecancer.2018.ed76
|View full text |Cite
|
Sign up to set email alerts
|

Does the oncology community have a rejection bias when it comes to repurposed drugs?

Abstract: Among the various measures proposed to combat the challenge of financial toxicity in cancer care, an important strategy is the use of lower-priced drugs instead of expensive alternatives. However, the oncology community seems to either ignore or more readily reject cheaper drugs in cancer care compared to more expensive alternatives. In this commentary, we present three examples of lower-priced drugs rejected or ignored by the oncology community and contrast this with three expensive drugs where persistent opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Consequently, ethical issues arose during the METTEN study trial based on the recommended standard of care supported by national and international guidelines with a neoadjuvant combination of taxane-containing chemotherapy and a dual blockade of trastuzumab and pertuzumab. Moreover, we cannot exclude the possibility that a rejection bias might exist against the repurposing of generic non-cancer metformin as oncological treatment when confronted to commercially developed anti-cancer drugs [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ethical issues arose during the METTEN study trial based on the recommended standard of care supported by national and international guidelines with a neoadjuvant combination of taxane-containing chemotherapy and a dual blockade of trastuzumab and pertuzumab. Moreover, we cannot exclude the possibility that a rejection bias might exist against the repurposing of generic non-cancer metformin as oncological treatment when confronted to commercially developed anti-cancer drugs [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the possibility that pancreatic cancer patients lack a hyperinsulinaemic state. Gyawali et al have provided a critical review of this study, arguing lack of study power, imbalance between the two groups and other confounding factors. A study by Zhao et al also randomly assigned 60 postmenopausal women with hormone receptor positive locally advanced or metastatic breast cancer to aromatase inhibitor plus metformin or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the possibility that pancreatic cancer patients lack a hyperinsulinaemic state. Gyawali et al 71 international prospective clinical trials indicates that metformin has the potential to improve clinical outcomes. 63 In contrast, a prospective Phase Ib study in nine patients with other (nonrenal) advanced cancers reported that a combination of everolimus and metformin was poorly tolerated.…”
Section: Potential Use In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a placebo-controlled phase II randomized clinical trial, metformin did not improve outcomes in patients with advanced pancreatic cancer [38]. However, this trial is quite controversial [39] since patients receiving metformin had more advanced disease (based on values of marker CA19.9), and they also received fewer treatment cycles. Results of another phase II trial in patients with advanced pancreatic cancer receiving standard systemic therapy with or without metformin (2 g daily) were reported [40] with no significant difference in 6-months progression-free, disease-free and overall survival between groups.…”
Section: Epidemiological Evidence Linking Diabetes and Cancer And Hypmentioning
confidence: 99%